L’iride e la Trinità: Osservazioni sulle fonti di Basilio, Epistula 38,5 - Verde, Francesco (Zeitschrift für antikes Christentum, 2018)
The focus of this contribution is to examine the section5 (Courtonne) of Basil’s Letter 38 devoted to the rainbow considered as a physical metaphor of the Trinity. The main purpose is to scrutinize the likely ancient pagan sources of Basil’s description of rainbow’s formation. The present article concludes by pointing out that the sources used by Basil could be traced back to Aristotle’s Meteorology and the Stoics (especially Posidonius), without denying an Epicurean influence too. The most interesting point is that the author of the letter seems to occasionally modify the ancient sources on the rainbow he consults in order to make the explanation of the rainbow consistent with his theological/Trinitarian scope. Since several studies confirmed the deep interest of Basil in the explanation of natural phenomena (always for theological and not scientific goals) on the basis of the theories of the ancient pagan Greek philosophers, it cannot be ruled out the possibility that Basil actually was the author of this epistle. This question is very problematic; it is not resolved but, in my opinion, it should also be reconsidered in the light of the part of the letter devoted to the comparison with the rainbow.